2017
DOI: 10.1136/bmjopen-2017-018169
|View full text |Cite
|
Sign up to set email alerts
|

Primary care management of headaches and how direct-access MRI fits: a qualitative study of UK general practitioners’ views

Abstract: ObjectivesTo develop a better understanding of general practitioners’ (GPs) views and experiences of the management of patients with headaches and use of direct-access MRI scans, and observe outcomes of an educational session offered by a GP with a special interest (GPwSI) to GPs.DesignA qualitative study using semistructured interviews, analysed using thematic analysis. A GPwSI in headaches visited practices delivering a talk on headache medication, diagnosis and management.SettingSixteen (16) primary care fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Once a serious underlying problem had been eliminated by scanning, an equal number of patients in both neurology and GP pathways focused on the need to relieve pain. According to GPs, this is easier once an underlying concern for serious pathology such as a brain tumour is eliminated 13. Our evidence supports this, but without follow-up interviews this cannot be confirmed in the long run.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Once a serious underlying problem had been eliminated by scanning, an equal number of patients in both neurology and GP pathways focused on the need to relieve pain. According to GPs, this is easier once an underlying concern for serious pathology such as a brain tumour is eliminated 13. Our evidence supports this, but without follow-up interviews this cannot be confirmed in the long run.…”
Section: Discussionmentioning
confidence: 48%
“…Given that resources and capacity are limited, a fear among policy-makers and providers is that demand for imaging and referral will rise from patients. GPs raised the lack of specialist input as another disadvantage of direct access, which may hinder in reassuring patients after a normal scan 13. In our previous study, we found that added training with an educational course regarding headache and direct imaging increased GP confidence in managing headache 13.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Training packages have been tested for headache management in primary care to help combat neurophobia. GPs who took part in the training said they felt more equipped with managing headache [100]. The same process could be evaluated for epilepsy.…”
Section: Contextualising the Findingsmentioning
confidence: 99%